A prospective study on geriatric abdominal surgical emergencies - Chavan, Deepak R.; Kannur, Shailesh; Metan, B. B.; Kullolli, Girish (International Journal of Research in Medical Sciences, 2017)
Background: Geriatric population is a special subgroup of population undergoing emergency abdominal surgeries. Both higher age group and emergency surgical procedure are considered as high risk factors. In this study, we study the most common cause for geriatric population to undergo an emergency abdominal surgery and the therapeutic outcomes. Methods: All the patients aged more than 60 years coming to surgical department, BLDEU’s hospital with acute abdominal conditions. Study period was from Jan 2010 to Jan 2013. All patients aged more than 60 years old admitted with abdominal emergency conditions in department of surgery. Geriatric patients coming with blunt trauma of abdomen also included. Exclusion criteria were immunocompromised patients. Results:128 patients aged 60 years or more who presented with abdominal emergency surgical conditions were studied. Most common cause for emergency abdominal surgery was perforated peptic ulcer (38%) followed by intestinal obstruction (17%). The most common post-operative complication was surgical site infection (29%). Mortality rate was 17%. Most common cause of death was septic shock with multi organ dysfunction. Conclusion:Geriatric population is an important subgroup of population undergoing emergency abdominal surgeries. Most common cause is peptic ulcer perforation followed by intestinal obstruction due to adhesions. More than the age per say, the delay in presentation may be the cause for mortality in this age group. The therapeutic outcome in patients with co morbid factors like hypertension and diabetes mellitus in control, were similar to other patients.